Effect of elastin peptides on ion fluxes in mononuclear cells, fibroblasts, and smooth muscle cells. - Jacob, M P (1987)
Elastin peptides prepared by alcoholic potassium hydroxide degradation of highly purified fibrous elastin from bovine ligamentum nuchae (kappa-elastin) were shown to act on the ion channels of human monocytes, aorta smooth muscle cells, and skin fibroblasts. In small amounts (between 0.1 and 1 microgram/ml), elastin peptides strongly increased calcium influx and inhibited calcium efflux by an apparently calmodulin-dependent mechanism. They also were shown to increase sodium influx and to decrease rubidium influx in monocyte preparations obtained from human blood. Only the ouabain-sensitive portion of rubidium influx was inhibited. The action of elastin peptides is strongly concentration-dependent; the maximal activity observed in the above reactions was less than 1 microgram/ml. These results suggest that elastin peptides may play a role in the regulation of the biological activity of mesenchymal cells, in the proximity of which they are released by the action of elastase-type enzymes. Such enzymes were demonstrated in aorta smooth muscle cells (membrane-bound serine protease) and in fibroblasts (metalloprotease). Monocytes and polymorphonuclear leukocytes were also shown to carry elastase-type enzymes. The release of peptides from elastin by elastase-type enzymes and the action of such peptides on the ion fluxes through the cell membrane may well be involved in mechanisms of the modulation of the phenotype of mesenchymal cells during aging as well as in the development of age-dependent pathologies such as arterioclerosis.